Molecular Interactions of First and Second Tier Dendrimers, Anticancer Molecules, Analyzed with Densities and Viscosities of Their Aqueous Mixtures - Singh, Man; Bhattarai, Ajaya; Kale, R. K.; Gutpa, Shalini; Chatterjee, Sujeet Kumar; Gupta, K. C. (Journal of Nepal Chemical Society, 2012)
Densities and viscosities of Tridiethymalonatetriazine (2,4,6) (TDEMTA) 1st (G1) and Hexadiethylmalonatetriazine (2,4,6) (HDEMTA) 2nd (G2) tier dendrimers for 0.62 to 10 mg % aqueous solutions are reported at 298.15 K and 303.15 K temperatures. Their data were compared with those of Trichlorotriazine (TCT), Triacetotrizine (TAT) and Trihydroxytrizine (THT) used as markers in the study. The densities for G2 are higher values than of G1 but both the dendrimers showed higher densities than those of the solvent with stronger heteromolecular forces due to stronger solvation and Intramolecular multiple force theory (IMMFT). DOI: http://dx.doi.org/10.3126/jncs.v27i1.6440 J. Nepal Chem. Soc., Vol. 27, 2011 46-52 Uploaded date: 16 July, 2012